2003
DOI: 10.1128/jvi.77.17.9337-9345.2003
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 2 Virion Host Shutoff Protein Regulates Alpha/Beta Interferon but Not Adaptive Immune Responses during Primary Infection In Vivo

Abstract: Herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) are ubiquitous human pathogens that cause a variety of serious diseases. Primary HSV infections typically initiate at mucosal surfaces, where lytic replication in epithelial cells generates mucosal lesions. Peripheral replication amplifies the virus load and increases uptake of virus into sensory nerve termini. Establishment of latent infections in sensory neurons secures shelter for the virus throughout the life of the host. Periodic reactivations result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 57 publications
(52 reference statements)
3
91
2
Order By: Relevance
“…However, the effect is not as striking as would have been expected if the interferon response were the main target of vhs. In contrast, recent studies by Murphy et al (38) demonstrate that the virulence of HSV-2 vhs mutants is almost fully restored in these mutant mice. The effect is specific to vhs, as the host mutation did not restore virulence to an HSV-2 mutant lacking thymidine kinase.…”
Section: Biological Roles Of Vhsmentioning
confidence: 50%
“…However, the effect is not as striking as would have been expected if the interferon response were the main target of vhs. In contrast, recent studies by Murphy et al (38) demonstrate that the virulence of HSV-2 vhs mutants is almost fully restored in these mutant mice. The effect is specific to vhs, as the host mutation did not restore virulence to an HSV-2 mutant lacking thymidine kinase.…”
Section: Biological Roles Of Vhsmentioning
confidence: 50%
“…12,13 The multiplicity of pattern recognition receptors (PRRs) detecting HSV necessitates a robust ability of the virus to effectively block multiple innate signaling pathways to survive. Previous studies identified several HSVencoded mechanisms that interfere with antiviral host immunity including nonspecific degradation of host mRNA by the RNAse VHS, 14 inhibition of PKR by US11 15 and ␥34.5, 16 inhibition of MHC-I peptide loading by ICP47, 17,18 and suppression of interferon response by ICP0. 19,20 However, to date, no HSV-encoded protein has been shown to interfere with TLR responses.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-␣␤ is induced quickly and efficiently in many types of cells upon infection by various viruses (12,13), and limits virus replication by establishing an antiviral state in uninfected cells (14). Mice deficient in IFN-␣␤ receptor (IFN-␣␤R) are much more susceptible to viral infection (15,16); replication and virulence of profoundly attenuated viruses are largely restored to levels of wild-type virus in mice lacking the IFN-␣␤R (17).…”
mentioning
confidence: 99%